RH diversity in Mali: characterization of a new haplotype RHD*DIVa/RHCE*ceTI(D2). Issue 6 (10th April 2015) - Ba, Alhassane; Beley, Sophie; Chiaroni, Jacques; Bailly, Pascal; Silvy, Monique
Abstract : BACKGROUND: Knowledge of RH variants in African populations is critical to improving transfusion safety in countries with populations of African ancestry and to providing valuable information and direction for future development of transfusion in Africa. The purpose of this report is to describe RH diversity in individuals from Mali. STUDY DESIGN AND METHODS: Blood samples collected from 147 individuals self‐identified as Dogon and Fulani were analyzed for Rh antigens and alleles. RESULTS: The most common RHD allele variant was RHD*DAU0 . Five predicted partial‐D phenotypes were attributed to RHD*DAU3 or RHD*DIVa . Neither RHD*DAR nor RHD*DIIIa was found. Investigation of RHCE revealed three predicted partial‐e antigens encoded by RHCE*ce(254G) in trans to RHCE*cE . Regarding C antigen, 28 Fulani typed as C+ and 16 of 28 harbored at least one RHCE*Ce‐D(4)‐ce, two being homozygous and predicted to show a rare RH:32, −46 phenotype. A new RHCE*ceTI with replacement of Exon 2 by RHD ( RHCE*ceTI(D2)) was identified in Dogon and was identified by inheritance study to be in cis to RHD*DIVa . These samples typed C– with anti‐C polyclonal antibody and monoclonal antibodies (MoAbs) MS24, P3X2551368+MS24, and MS273, but positive with anti‐RhCe MoAb‐BS58. The same pattern was observed in sample with RHD*DIVa/RHCE*ceTI . CONCLUSION: Our survey indicated an uneven distribution of RH variant alleles between Dogon and Fulani, suggesting that study in well‐documented cohorts is warranted. A high incidence of predicted partial‐C phenotype encoded by RHCE*Ce‐D(4)‐ce was found in Fulani. Further study will also be needed to clarify the clinical significance of the new DIVa/ceTI(D2) haplotype encoding partial D and variant ce antigens.